Ajatollah Chomeini i rewolucja islamska. Droga do władzy i jej skutki - Mikrut, Szymon (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is dedicated to the events known in historiography as the Iranian Islamic Revolution, led by Ayatollah Khomeini. Its aim is to analyze the political, social, and economic changes that occurred after the transition to an Islamic republic, as well as to compare them with the modernist reforms carried out by the Pahlavi dynasty from the 1920s, modeled on Western countries. Additionally, the article highlights the role played by Khomeini and the ideology he created, which became the foundation for changes in the country. The study also compares Iran`s international position during the Pahlavi era and after the Revolution, simultaneously pointing to Iran`s close ties with Western countries as one of the reasons for the monarchy?s overthrow.
Keywords: rewolucja islamska; Chomeini, Ruhollah Musawi ajatollah (przywódca duchowny i polityczny Iranu; 1900-1989); dynastia Pahlawich; Islamic Revolution; Pahlavi dynasty